Effect of platelet-rich fibrin on epidural fibrosis and comparison to ADCON® Gel and hyaluronic acid - Esra Demirel; Kadri Yildiz; Kenan Çadirci; Hayati Aygün; Eyüp Şenocak; Betül Gündoğdu (Acta Orthopaedica et Traumatologica Turcica, 2018)
Objective: In this experimental study, PRF (Platelet Rich Fibrin), HA (Hyaluronic Acid) gel and ADCON® Gel were compared in terms of preventing epidural fibrosis. Methods: Twenty-eight Sprague–Dawley rats (mean weight, 400–450 g) were divided into 4 groups. L3-L4 laminectomy was performed in each group. Following laminectomy, Adcon® Gel, HA gel and PRF were applied onto the surgery site locally in Group 1, 2 and 3, respectively. Group 4 was maintained as control without any local application. After five weeks, L3-L4 vertebrae were removed totally and taken to histopathological evaluation for epidural fibrosis, acute inflammatory cell density, chronic inflammatory cell density, hemorrhage, angiogenesis and new bone formation. Results: Acute inflammation cell density, angiogenesis, and new bone formation levels were comparable among the study groups (p > 0.05). However, new bone formation was higher in the PRF group. Epidural fibrosis and chronic inflammatory cell density were significantly lower in the PRF group (p < 0.05). Conclusion: We concluded that PRF contributed to hemostasis and prevented epidural fibrosis. Keywords: Epidural fibrosis, PRF, ADCON gel, Hyaluronic acid gel, Histological comparison